Studi Prosedur Pemeliharaan Arsitektural Bangunan Bengkel Berdasarkan Peraturan Menteri Pekerjaan Umum Nomor 24/Prt/M/2008 - Ramadhani, Viola Malta; Nurmalasari, Riana; Athalla Sidharta, Rassya; Amin, Rais (Riviera Publishing, 2025)
Workshop is one type of building that accommodates unusual activities and requires special handling. Therefore, in carrying out workshop building maintenance, a guideline is needed. One of them is SOP (Standard Operating Procedure). SOP is useful for ensuring consistency and efficiency in workshop building maintenance. Maintenance activities will be recorded properly. In addition, the existence of SOP can be a guideline for building maintenance according to applicable provisions. One of the provisions related to building maintenance is Permen PU No. 24/PRT/M/2008 concerning Guidelines for Building Maintenance and Care. This study aims to compile a Standard Operating Procedure (SOP) for workshop building maintenance based on Permen PU No. 24/PRT/M/2008. The research method used in this study is descriptive qualitative. Data collection was carried out through observation and interviews. Observations were made in the workshop building to see the construction specifications. Meanwhile, interviews were conducted with users and building managers to find out the activities in the building. The results of this study are SOPs for building maintenance that can be applied to workshops.